Investigating the role of hypothetical protein (AAB33144.1) in HIV-1 virus pathogenicity: A comparative study with FDA-Approved inhibitor compounds through In silico analysis and molecular docking - Md. Imran Hossain; Anika Tabassum Asha; Md. Arju Hossain; Shahin Mahmud; Kamal Chowdhury; Ramisa Binti Mohiuddin; Nazneen Nahar; Saborni Sarker; Suhaimi Napis; Md Sanower Hossain; A.K.M. Mohiuddin (Heliyon, 2024)
Aim and objective: Due to the a lot of unexplored proteins in HIV-1, this research aimed to explore the functional roles of a hypothetical protein (AAB33144.1) that might play a key role in HIV-1 pathogenicity. Methods: The homologous protein was identified along with building and validating the 3D structure by searching several bioinformatics tools. Results: Retroviral aspartyl protease and retropepsin like functional domains and motifs, folding pattern (cupredoxins), and subcellular localization in cytoplasmic membrane were determined as biological activity. Besides, the functional annotation revealed that the chosen hypothetical protein possessed protease-like activity. To validate our generated protein 3D structure, molecular docking was performed with five compounds where nelfinavir showed (−8.2 kcal/mol) best binding affinity against HXB2 viral protease (PDB ID: 7SJX) and main protease (PDB ID: 4EYR) protein. Conclusions: This study suggests that the annotated hypothetical protein related to protease action, which may be useful in viral genetics and drug discovery.